Effects of silicon on heavy metal uptake at the soil-plant interphase: A review - Khan, Imran; Awan, Samrah Afzal; Rizwan, Muhammad; Ali, Shafaqat; Hassan, Muhammad Jawad; Brestic, Marian; Zhang, Xinquan; Huang, Linkai (Ecotoxicology and environmental safety, 2021)
Silicon (Si) is the second richest element in the soil and surface of earth crust with a variety of positive roles in soils and plants. Different soil factors influence the Si bioavailability in soil-plant system. The Si involves in the mitigation of various biotic (insect pests and pathogenic diseases) and abiotic stresses (salt, drought, heat, and heavy metals etc.) in plants by improving plant tolerance mechanism at various levels. However, Si-mediated restrictions in heavy metals uptake and translocation from soil to plants and within plants require deep understandings. Recently, Si-based improvements in plant defense system, cell damage repair, cell homeostasis, and regulation of metabolism under heavy metal stress are getting more attention. However, limited knowledge is available on the molecular mechanisms by which Si can reduce the toxicity of heavy metals, their uptake and transfer from soil to plant roots. Thus, this review is focused the following facets in greater detail to provide better understandings about the role of Si at molecular level; (i) how Si improves tolerance in plants to variable environmental conditions, (ii) how biological factors affect Si pools in the soil (iii) how soil properties impact the release and capability of Si to decrease the bioavailability of heavy metals in soil and their accumulation in plant roots; (iv) how Si influences the plant root system with respect to heavy metals uptake or sequestration, root Fe/Mn plaque, root cell wall and compartment; (v) how Si makes complexes with heavy metals and restricts their translocation/transfer in root cell and influences the plant hormonal regulation; (vi) the competition of uptake between Si and heavy metals such as arsenic, aluminum, and cadmium due to similar membrane transporters, and (vii) how Si-mediated regulation of gene expression involves in the uptake, transportation and accumulation of heavy metals by plants and their possible detoxification mechanisms. Furthermore, future research work with respect to mitigation of heavy metal toxicity in plants is also discussed. •Root application of silicon (Si) improved soil physical and chemical properties that help in decomposition of organic matter.•Exogenous Si efficiently restricted the heavy metals (HMs) uptake and translocation within the plants.•Si improved the root morphology and competed with HMs for uptake in root cells and translocation to xylem vessels.•Si actively participates in plant growth with respect to all aspect under HM toxicity.